Evaluation of fly ashes for the removal of cu, ni and cd from acidic waters (2010)
The presence of sulphides in many mine wastes and the formation of acid mine drainages (AMD) has been widely recognized as one of the great environmental problems nowadays. Waters from many of the abandoned mines, with thousands of cubic meters of residue scattered in dumps and ponds, are affected by this type of pollution characterized by its acidity, high contents of sulphates and heavy metals such as Fe, Mn, Al, Cu, Ni, Cd. This study was designed to study the effect of use flying ash coming from Power Stations as a neutralizer for acidic waters resulting from this type of abandoned facilities. In this study, and due to the heterogeneity of the contaminants present, we have studied the removal of Ni, Cu and Cd. Different parameters were studied: metal concentration and pH of the solution to be treated, time reaction and pulp density. Fly ash can be used as a neutralization/fixation agent. Fly ash will add alkalinity and increase the pH on contacting AMD. This will result in precipitation of metal hydroxides.